Is Telemedicine Suited for Lower Extremity Pathologies? An Analysis of Non-Urgent Follow-Up in a Foot and Ankle Practice. Issue 4 (22nd October 2020) - Manz, Wesley J.; Goel, Rahul; Fakunle, Omolola; Labib, Sameh A.; Bariteau, Jason T.
Category: Other; Ankle; Hindfoot; Midfoot/Forefoot Introduction/Purpose: A lack of access to care is predictably associated with negative outcomes in foot and ankle surgery. Despite recent advances in telecommunication technologies, the field of orthopaedics has been slow to adopt these resources in offsetting barriers to care. The COVID-19 pandemic has forced departments to change their clinical approach, lending unprecedented opportunity to better understand how telehealth may bridge this care gap in foot and ankle practices. The purpose of this study was to assess patient-reported outcomes of telemedicine encounters, including comfort and patient satisfaction. Our hypothesis was that patients would be significantly less satisfied with telemedicine when compared to in-office appointments for all non-emergent visit types. Methods: Retrospective analysis of patients seen via telemedicine between April 13, 2020, to June 19, 2020, by one surgeon in the Emory Orthopedics Foot and Ankle department was conducted. Patients were contacted by one of the study authors via telephone to complete a questionnaire; satisfaction and other visit characteristics were assessed with a modified Likert scale from 1 to 5. Patients were designated as either 'New' or 'Established' based on whether or not they had completed an in-office clinic visit within the last year. Anatomy and pathology of disorder were determined by chief complaint and billing code. Patient demographics were recorded, and data were analyzed using paired and independent t-tests for parametric continuous data, Fisher's exact and chi-square tests for non-continuous data. Results: 338 eligible patients were contacted via telephone, with 216 (63.9%) completing the telemedicine questionnaire. The patient cohort had an average age of 50.6 (19-84) years old and was 73.6% female (n=159). Overall mean satisfaction for telemedicine visits (4.69) was significantly lower than in-office visits (4.86) (p<0.001). In a subgroup analysis of patient satisfaction, patients seeking fracture care had significantly higher telemedicine satisfaction when compared to those receiving non-fracture care (4.90 vs. 4.64, p=0.001). Telemedicine satisfaction was also significantly greater in patients traveling more than 50 miles from their home to clinic (4.96 vs. 4.67, p<0.001). Patients with median household income less than the Georgia state median ($55, 679) were more satisfied with their telemedicine visits than those with greater income, though the difference was non-significant. Conclusion: our data suggest those with significantly hindered mobility such as increased distance from clinic, lower socioeconomic status, and those seeking care for fractures had higher telemedicine satisfaction than their peers. Further study is needed to detail the precise and safe use of telemedicine in practice, but these data illuminate the high ceiling telemedicine offers in expanding patient care. Our hope is that this study aids as a supportive rationale for the continued use of telehealth visits past the period of the pandemic and encourages a more nuanced view of what visit types may be best-suited for telehealthcare